PROFILES OF PROBLEMATIC SOILS AND SPATIAL DISTRIBUTION: IMPLICATION ON FOUNDATION CONSTRUCTION IN PARTS OF KOSOFE LAGOS, SOUTHWESTERN NIGERIA. - Oloruntola, Moroof Olasunbo; Bayewu, Olateju O; Kehinde, Kolawole; Obasaju, Daniel Opemipo; Mosuro, Ganiyu (GeoScience Engineering, 2018)
Geotechnical data were complemented with the geophysical investigation and employed to delineate problematic soils in parts of Kosofe Lagos, Southwestern Nigeria. The study area was chosen because of known issues regarding cracks in buildings and differential settlement of infrastructures founded on soils in the area. The aim is to generate profiles and maps of the spatial distribution of the subsurface soils to aid in foundation planning. Forty-eight borehole logs and nine Vertical Electrical Soundings were compiled to delineate the different subsurface lithology which includes peat, clay, and sand. The results showed that the peat layer has a maximum thickness of about 18.25 m but absent in some boreholes. This is underlain by clay unit with thickness ranging between 2.50-28.50 m. Sand unit constitutes the third layer delineated with a maximum thickness of 14 m. There is a general thickening of peat soils in the northern parts, especially around the streams in the area, which is instructive on the role of stream in the formation of the peat. The clay, on the other hand, is thickest around the northeastern and southeastern parts. The soil profiles generated reveal that the area is underlain by thick peat and clay having significant lateral, vertical variation and rapidly changing lithological facie over short distances. The extensive occurrence of these poor engineering soils calls for adequate engineering precaution in designs of building foundations. Keywords: VES, geotechnical borehole profiles, problem soils, foundation, southwestern Nigeria https://doi.org/10.2478/gse-2018-0017